Job Satisfaction and Quality of Work Life: Impact on Industrial Relations in Textile Units in Kannur District, Kerala - Rajesh S AND Manoj P K
The consequences of Industrial disputes will be harmful to the promoters of industries, workers, economy and the nation as a whole, because such disputes result in loss of productivity, profits, market share and even closure of the plant. Hence, Industrial disputes need to be averted by all means. Organizations are required to adopt a strategy to curb the conflicts in the initial stages itself. Industrial disputes are affecting the industrial development and industrial relations systems. This article makes a closer look into the statistics on industrial disputes in Kerala and analyses its causes, trends, implications on various stake-holders, and also consequences on industrial relations during a decade 2001–2010. The paper concludes that there is high degree of association between industrial dispute facts and challenges to cordial industrial relations in Kerala state.